Effects of frequency and idiomaticity on second language reading comprehension in children with English as an additional language - Kan, Rachel T. Y.; Murphy, Victoria A. (Studies in Second Language Learning and Teaching, 2020)
Vocabulary plays an important role in reading comprehension in both the L1 and the L2 (Murphy, 2018). In measuring vocabulary knowledge, however, researchers typically focus on mono-lexical units where vocabulary assessments tend not to take into account multi-word expressions which include phrasal verbs, collocations, and idioms. Omitting these multi-word lexical items can lead to an over-estimation of comprehension skills, particularly in reading. Indeed, adult learners of English comprehend texts containing a larger number of multi-word expressions less well compared to texts containing fewer of these expressions, even when the same words are used in each text (Martinez & Murphy, 2011). To investigate whether children learning English as an additional language (EAL) face a similar challenge, two reading comprehension tests were administered to EAL and monolingual (non-EAL) English-speaking children in primary school. Both tests contained the same common words, but whereas in one test some of the words occurred in multi-word expressions, in the other test they did not. Reading comprehension was significantly reduced for both groups of children when multi-word expressions were included. Monolingual participants generally performed better than children with EAL on both tests further suggesting that children with EAL may face a particular disadvantage in English reading comprehension. These results are discussed within the context of the importance of developing rich vocabulary knowledge in all children, and especially emergent bilingual children, within primary school and beyond.